Preliminary study of donor volume changes after dual-graft liver transplantation in rats - Wang, Dan; Ma, Yanling; Gu, Baohong; Li, Xuemei; Yu, Yang; Zhang, Ying; Chen, Hao (Frontiers in Immunology, 2023)
Dual-graft liver transplantation (DGLT) expands the pool of donors, ensures the safety of the donors and treats a potential small for size syndrome (SFSS). However, some of the recipient graft showed atrophy. The cause and mechanism of the unbalanced proliferation and atrophy of dual grafts after clinical DGLT have not been clarified. We established and optimized the rat model of DGLT to explore the causes of growth unbalance. Continuously and dynamically observed bilateral graft volume and portal vein blood flow changes by magnetic resonance imaging (MRI) and ultrasound (US).We detected liver function indexes: alanine aminotransferase (ALT), aspartate aminotransferase (AST), lactate dehydrogenase (LDH), total bilirubin (TBIL), direct bilirubin (DBIL), and indirect bilirubin (IBIL). Liver samples from receptors were obtained for morphology, and apoptosis was measured by RT-PCR and western blot.Optimization of the model improved the 7-day survival rate of from former 58.3% to 87.5%, and the 30-day survival rate was 68.8%. The volume of the right graft gradually increased, and the left graft atrophied during the 30-day observation period. The portal blood flow of the left graft gradually decreased until 30th day (0.13 ± 0.01ml/s) compared with sham group (0.63±0.05 ml/s), and right graft significantly increased in the 30th day (0.75±0.11ml/s). The liver function initially increased and then recovered.The total volume (12.52±1.60ml vs 4.47±0.08ml) and weight (12.09±1g vs 4.91±0.18g) of the graft increased significantly compared to pre-transplantation and reached the level of the sham operation group on the 30th day. The volume and weight of the right graft increased more than those of the left graft (P<0.05). There was more inflammatory cell infiltration in the left graft, and the right graft had obvious proliferation of hepatocytes and mature bile duct cells. Left grafts were more prone to apoptosis than right grafts (P<0.05). In conclusion, growth of right graft is superior to the left, after double liver transplantation, perfusion blood flow and apoptotic may be the reason contributing to the volume differences in dual grafts.